OVERVIEW ON THE RESEARCH SITUATION OF THE RIP CURRENT AT THE SEA BEACHES OF VIETNAM AND IN THE WORLD - Xuan, Nguyen Ba (Vietnam Journal of Marine Science and Technology, 2009)
This paper presents an overview of the research situation of the rip current occurred at the sea beaches of Vietnam and in the world. Through the study and evaluation of collected materials, it found that: the rip current is not a mysterious phenomenon, that is a special component of the general current having the direction apart from the coast and usually causes the death accidents when people swimming in the coastal sea. It was formed in the surf zone and often be in a fluctuation, which depends on the conditions of the terrain coast, sea bottom and sea wave created by the influence of the changed weather conditions ... This paper also presents a summary of the reasons and mechanisms formatted the rip current and the methods to identify and guide how to prevent the rip currents when falling in the zone of their action.